Difficulties of Mauritanian criminal law in confronting modern technology crimes - Mohamed Said Alem (International Journal of Law Research and Studies, 2026)
This study addresses the challenges faced by Mauritanian criminal law in confronting modern technology-related crimes, through an analysis of both the substantive and procedural frameworks of the Mauritanian criminal justice system. It highlights the gaps inherent in the criminal policy adopted by the legislator in this field. The research demonstrates that the enormous technological development has generated new patterns of criminal behavior, while Mauritanian criminal law continues to rely on traditional mechanisms that hinder an effective response. The study also focuses on the difficulties stemming from the nature of cybercrime, the weakness of technical and evidentiary tools, and the lack of specialized expertise among investigative authorities. In addition, the research points to the problem of institutions’ reluctance to report incidents and the challenges of international cooperation in cross-border cybercrimes. Finally, the study presents a set of practical proposals and solutions aimed at improving the drafting of national legislation related to individual rights and freedoms—such as the confidentiality of communications and the right to privacy—regulating the rules governing lawful telephone interception and electronic surveillance, expanding judicial powers in electronic searches, establishing a national cyber security authority, and acceding to the Budapest Convention to enhance international cooperation in combating cybercrime. The study also calls for the training of investigative and prosecutorial authorities in this field, in order to strengthen their ability to understand and apply legislative texts in light of contemporary communication technologies.